Descending pathways from the superior colliculus mediating autonomic and respiratory effects associated with orienting behaviour. (2nd December 2022) - Lynch, Erin; Dempsey, Bowen; Saleeba, Christine; Monteiro, Eloise; Turner, Anita; Burke, Peter G. R.; Allen, Andrew M.; Dampney, Roger A. L.; Hildreth, Cara M.; Cornish, Jennifer L.; Goodchild, Ann K.; McMullan, Simon
Abstract : Abstract: The ability to discriminate competing external stimuli and initiate contextually appropriate behaviours is a key brain function. Neurons in the deep superior colliculus (dSC) integrate multisensory inputs and activate descending projections to premotor pathways responsible for orienting, attention and defence, behaviours which involve adjustments to respiratory and cardiovascular parameters. However, the neural pathways that subserve the physiological components of orienting are poorly understood. We report that orienting responses to optogenetic dSC stimulation are accompanied by short‐latency autonomic, respiratory and electroencephalographic effects in awake rats, closely mimicking those evoked by naturalistic alerting stimuli. Physiological responses were not accompanied by detectable aversion or fear, and persisted under urethane anaesthesia, indicating independence from emotional stress. Anterograde and trans‐synaptic viral tracing identified a monosynaptic pathway that links the dSC to spinally projecting neurons in the medullary gigantocellular reticular nucleus (GiA), a key hub for the coordination of orienting and locomotor behaviours. In urethane‐anaesthetized animals, sympathoexcitatory and cardiovascular, but not respiratory, responses to dSC stimulation were replicated by optogenetic stimulation of the dSC–GiA terminals, suggesting a likely role for this pathway in mediating the autonomic components of dSC‐mediated responses. Similarly, extracellular recordings from putative GiA sympathetic premotor neurons confirmed short‐latency excitatory inputs from the dSC. This pathway represents a likely substrate for autonomic components of orienting responses that are mediated by dSC neurons and suggests a mechanism through which physiological and motor components of orienting behaviours may be integrated without the involvement of higher centres that mediate affective components of defensive responses. Key points: Neurons in the deep superior colliculus (dSC) integrate multimodal sensory signals to elicit context‐dependent innate behaviours that are accompanied by stereotypical cardiovascular and respiratory activities. The pathways responsible for mediating the physiological components of colliculus‐mediated orienting behaviours are unknown. We show that optogenetic dSC stimulation evokes transient orienting, respiratory and autonomic effects in awake rats which persist under urethane anaesthesia. Anterograde tracing from the dSC identified projections to spinally projecting neurons in the medullary gigantocellular reticular nucleus (GiA). Stimulation of this pathway recapitulated autonomic effects evoked by stimulation of dSC neurons. Electrophysiological recordings from putative GiA sympathetic premotor neurons confirmed short latency excitatory input from dSC neurons. This disynaptic dSC–GiA–spinal sympathoexcitatory pathway may underlie autonomic adjustments to salient environmental cues independent of input from higher centres. Abstract : Abstract figure legend Salient acoustic and visual stimuli elicit stereotypical responses with motor, respiratory and cardiovascular components. Here we show that optogenetic stimulation of the deep caudolateral superior colliculus (SC) elicits orienting and arousal that is accompanied by tail vasoconstriction and increased respiratory activity in awake rats. Using a combination of electrophysiology in urethane‐anaesthetized rats and anterograde and trans‐synaptic viral tracing, we reveal a monosynaptic tecto‐medullary pathway from the superior colliculus to spinally projecting neurons in the gigantocellular reticular nucleus (GiA) that contributes to the sympathetic and cardiovascular components of SC responses. We propose that this pathway likely mediates components of innate motor and physiological responses to ecologically relevant naturalistic stimuli.